2009
DOI: 10.1021/jp908482q
|View full text |Cite
|
Sign up to set email alerts
|

Density Functional Theory Study of Iron and Cobalt Carbides for Fischer−Tropsch Synthesis

Abstract: Carbides are important phases in heterogeneous catalysis. However, the understanding of carbide phases is inadequate: Fe and Co are the two commercial catalysts for Fischer-Tropsch (FT) synthesis, and experimental work showed that Fe carbide is the active phase in FT synthesis, whereas the appearance of Co carbide is considered as a possible deactivation cause. To understand very different catalytic roles of carbides, all the key elementary steps in FT synthesis, that is, CO dissociation, C 1 hydrogenation, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
154
1
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 169 publications
(166 citation statements)
references
References 59 publications
8
154
1
3
Order By: Relevance
“…8 and Supplementary Table 4). Under identical reaction conditions at 443 K, the r 0 of the RQ Fe-w catalyst (Table 3, entry 6) is only about 25% of that of the e-Fe 2 C-dominant RQ Fe catalyst, which is consistent with theoretical predictions that e-Fe 2 C is more active than w-Fe 5 C 2 in FTS 25,27 .…”
Section: Article Nature Communications | Doisupporting
confidence: 85%
See 1 more Smart Citation
“…8 and Supplementary Table 4). Under identical reaction conditions at 443 K, the r 0 of the RQ Fe-w catalyst (Table 3, entry 6) is only about 25% of that of the e-Fe 2 C-dominant RQ Fe catalyst, which is consistent with theoretical predictions that e-Fe 2 C is more active than w-Fe 5 C 2 in FTS 25,27 .…”
Section: Article Nature Communications | Doisupporting
confidence: 85%
“…According to a volcano-plot for metal-CO bond strength versus FTS activity for iron and cobalt 27 , increasing the carbon content in iron carbide will weaken the Fe-CO bonding and hence enhance the activity. These works prompt us to develop a new catalytic material that is constituted by e-Fe 2 C holding promise as an active catalyst in LTFTS.…”
mentioning
confidence: 99%
“…3.1. The CH x(x = 0-3) hydrogenation on Co 2 C (001) as also studied by Cheng et al [144] and they reported that the methane selectivity is higher on cobalt carbides compared with metallic Co, indicating that metallic cobalt is the preferred active site for FTS. Recently, similar geometrical and energetic information of CH x(x = 0-3) hydrogenation were also derived for Co (0001), Co (10)(11)(12) and Co (11)(12)(13)(14)(15)(16)(17)(18)(19)(20) by Li and coworkers [115], indicating the CH x(x = 0-3) hydrogenation are not significantly affected by the local structure.…”
Section: Methane Selectivitymentioning
confidence: 68%
“…CH 2 are still the most possible chain growth pathways for C 2 ? C 1 coupling based on Table 4 The activation energies of elementary steps involved in chain propagation and termination for the carbide mechanism a Ref [116] b Ref [36] c Ref [119] d Ref [144] e Ref [117], where the data in the parentheses were calculated on Co (0001) 13 CO and H 2 , the isotopic content was monitored for propane formation. The carbide mechanism should produce all kinds of combination with 12 C and 13 C in propane; the CO insertion mechanism should produce 12 C-13 C-13 C and 13 C-13 C-13 C and the hydroxyl mechanism should produce 13 C-13 C-13 C. Based on the composition of the produced propane, it was concluded that only the carbide mechanism could produce the product compositions and the other mechanisms were therefore excluded.…”
Section: Chain Growthmentioning
confidence: 99%
See 1 more Smart Citation